A visibilidade da UFSM no facebook: (inter)relações entre universidade, jornais e usuários-mídia. - Scheid, Daiane (2017)
The research studies visibility on digital social media, especially the Federal University of Santa Maria (UFSM) visibility on the Facebook social network website. We highlight the context of mediatization (HJARVARD, 2014; SODRÉ, 2007) and the ecosystem formed by communication media in which digital social networks take part (RECUERO, 2010). Thus, we investigate the phenomenon of visibility (FOUCAULT, 2014; THOMPSON, 2008a, 2008b; BRUNO, 2013) in the context of organizations (BARICHELLO, 2009, 2014; OLIVEIRA; PAULA, 2007; TERRA, 2011). The general objective of the research is to examine the UFSM visibility on Facebook from the (strategic) relationship among the University, newspapers and social network users (media users). Therefore, we list the following specific objectives: to contribute in order to broaden knowledge about the organizational visibility in the context of digital social media; to characterize the UFSM visibility in the fan pages: UFSM, Diário de Santa Maria, and A Razão; and to analyze discourse behaviors in the fan pages in order to understand the relationships among UFSM, newspapers and media users in the construction/from the University visibility in this ambience. The investigation adopts the qualitative orientation (GIL, 2007; OLIVEIRA, 2012) based on the Computer-mediated Discourse Analysis approach (HERRING, 2004, 2007). The study includes the application of methodological techniques of simple observation (GIL, 2007), systematic/covered and non-participative observation (GIL, 2007; JHONSON, 2010), interview (GIL, 2007), and literature review (GIL, 2007; OLIVEIRA, 2012). The dissertation is structured into four chapters which integrate theoretical, methodological and analytical elements, besides the introduction and the final considerations. Regarding the presence of UFSM on the Facebook social network website, we identify that it is linked to the informational appeal to the detriment of the relational appeal; the UFSM visibility in this network is expanding; UFSM demonstrates autonomy to promote its visibility in digital environments; the presence of UFSM in the network is ruled by its press release actions. As for the (inter)relations among UFSM, newspapers and media users, we emphasize that they are cooperative; however, they are not much dialogic, and are rarely strategic.